Gambaran Pengetahuan dan Perilaku Remaja Tentang Obesitas di SMA Negeri 1 Kota Tarakan - Siti Khadijah Adhar; Haris Haris; Rohandi Baharuddin; Sriargianti Amir (Journal Borneo, 2022)
Obesity is one of the problems of adolescents who are influenced by factors such as poor eating patterns, unhealthy food choices, and lack of physical activity, thus triggering the accumulation of excess fat in the body, which can lead to the emergence of various types of non-communicable diseases and is one of the causes of death worldwide. This research was conducted to describe the knowledge and behavior of adolescents about obesity at SMA Negeri 1 Tarakan City. This research is descriptive. Sampling was carried out by non-probability sampling with quota sampling with 53 respondents. The results showed that the characteristics of the respondents based on age were the most in the 17-year category, with 28 (52.4%) respondents. Characteristics based on BMI showed that the majority had the most BMI obesity, as many as 27 (50.9) respondents. Characteristics based on genetics (heredity) obtained the most results in the category without a history of obesity, as many as 41 (77.4%) respondents, characteristics of respondents based on knowledge obtained partial results 46 (86.8%) have good knowledge, 3 (5.7%) have sufficient knowledge, 4 (7.5%) respondents lack knowledge, and the characteristics of respondents based on eating patterns show partial results on bad eating patterns of 38 ( 71.7%) of respondents. The conclusion of this study shows that adolescents aged 17 years have good knowledge about obesity and eating behavior.